Tormentas urbanas : escritas, errâncias e conversas fiadas na cidade - Silva, Maicon Barbosa (2012)
Among wanderings through the city, writing and conversation courses, this text is woven as a way of thinking and inventing the urban experience. A heterogeneous writing is put in the work, populated by rupture and fragments, bypassing of the attempts of homogenization directed to a dialectical synthesis of the differences inherent to the text. The concept of out, murmuring area that drag the writing, is articulated to the foreigner - anonymous character who writes and who gets in the bowels of the city, wandering through everyday immersed into forgetting and invisibility. The condition of foreigner is created in relation to the city, delineating a body that derives by the density of the metropolis, by the practiced spaces and by engendered times. The wandering becomes a research practice that takes away the foreigner, throwing it on the chance that plots lines and node in the town, a requirement that the process itself becomes an accomplice of the experiment. This wandering is put as an unhurried way of moving by the metropolis, which differs from other rhythms produced on the surface of everyday life, through which compounds short stories, partial, unfinished: story of a multiple present, constituted by many lines that is entangle with other times. In chit-chat that disperses through the streets, buses, public transportation terminals and the Rodoviária Velha, the urban experience is woven and unraveled: the city is taken by plots, fragmentary narratives that proliferate in many directions, interlacing their own daily lives. Some stories of the invention of Aracaju are articulated to the problematization, at present, some control strategies of spaces and the movement of bodies. But, despite the presence of power technologies, the city also aligned itself as a labyrinth whose paths of space and time are opened in a thousand directions. The city is produced as an area swept by heterogeneous forces, ambiguous and coexisting: wanderings and chit-chat are made in a urban world beset by planning disciplinary of the space, controls of the movement and visibility mechanisms. Guerrilla daily is crashed with insistence, disperses in small urban storm which scrambles the surface of the projected city that became labyrinth.